Mucins in the colorectal neoplastic spectrum with reference to conventional and serrated adenomas - Sibel PERÇİNEL and Berna SAVAŞ and Arzu ENSARİ and Işınsu KUZU and M. Ayhan KUZU and Mehmet BEKTAŞ and Hülya ÇETİNKAYA and Nazmiye KURŞUN (Turkish Journal of Gastroenterology, 2019)
-